Love Methapors in William Shakespeare’s Drama Romeo and Juliet - ahmad muhid (Universitas Aki, 2014)
An article appeared on a newspaper or magazine is interesting to read if the article is coloured with some figurative languages like metaphor, allegory, personification, metonymy, and the like.These elements will make sentences nice to read and at that moment they have driven away dull dry paragraphs. It is customary to fill the paragraphs with figurative languages, especially of metaphors if the piece of writing is of a literary work. But it is a challenge to insert few metaphors in every essay. Metaphor is comparing two objects to create a certain perception. Furthermore, metaphor may contain deeper understanding; in this way it needs extra effort to dig out the meaning from the lines. Tenor and vehicle of metaphor can be employed to understand the content embedded in a metaphor. In William Shakespeare’s drama of “Romeo and Juliet” of which is famous throughout the world for its everlasting love story, there can be found many metaphors of love. Some of them are discussed in this paper. Key words: metaphor, love, figurative language, tenor, vehicle.